Out-of-hospital cardiac arrest patients with implantable cardioverter-defibrillators: What are their outcomes?. (December 2020) - Li, Jie; Zhang, Yongshu; Long, Ming; Liu, Menghui; Zhang, Wanwan; Gu, Liwen; Su, Chen; Xiong, Yan; Wang, Lichun; Idris, Ahamed
Abstract: The aim of the study: To identify the prognostic factors and effects of implantable cardioverter-defibrillators (ICDs) in out-of-hospital cardiac arrest (OHCA) patients with ICDs because the clinical characteristics and outcomes of OHCA patients with ICDs are unknown. Methods: The North American Resuscitation Outcomes Consortium (ROC) Cardiac Epistry Version 3 dataset was analyzed. Eligible patients were divided into OHCA patients with and without ICDs. Multivariable regressions were employed to analyze. Results: Of 51, 634 eligible OHCA patients, 581 (1.13%) had implanted ICDs. Among them, 53 (9.1%) patients survived to hospital discharge, and 40 (6.9%) patients had favorable neurological outcome at hospital discharge. Multivariable regression showed ICDs were not associated with OHCA outcomes in the total OHCA patients. In the OHCA patients with ICDs, shockable initial emergency medical services (EMS)-recorded rhythms and the ICD-shock-only defibrillation pattern were independent favorable factors for survival to hospital discharge(OR = 3.3, 95%CI 1.7–6.2, P < 0.001; OR = 2.4, 95%CI 1.1–5.5, P = 0.035, respectively) and neurological outcome at hospital discharge (OR = 6.5, 95%CI 2.9–14.4, P < 0.001; OR = 3.6, 95%CI 1.4–9.1, P = 0.006, respectively). During field resuscitation in OHCA patients with ICDs, at least 34.9% of total patients and 64.6% of patients with initial EMS-recorded VT/VF rhythms needed additional external shocks. Conclusions: Shockable initial EMS-recorded rhythms and ICD-shock-only defibrillation pattern were independent factors for the favorable outcomes of OHCA patients with ICDs. ICDs were not associated with the outcomes of OHCA, and additional external shocks were needed in a substantial number of OHCA patients with ICDs during field resuscitation.